Problems of Legal Regulation Tourism Safety Problems and Ways to Solve Them - TATSIIENKO, Valerii; MIROSHNYKOV, Ivan; KROITOR, Volodymyr; BIRIYKOVA, Alevtina; ORZHYNSKA, Elvira; OPERUK, Vitalii (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.12.2(50).20, 2021)
The article provides a general description of the safety of tourism, namely: the history of the issue of ensuring safety in tourism is analyzed, the concept, types and tasks of tourism safety are revealed, and the classification of risks (threats) and sources of danger in the field of tourism is considered; defined the concept, structure and content of the administrative and legal institute of tourism safety, and also disclosed the legal regulation in the field of tourism safety; disclosed the concept and content of administrative and legal tourism safety regime, classify it into types (sub-regimes); describes the administrative and legal measures to ensure the safety of tourism; highlighted the main security problems in the field of tourism and formulate ways to solve them. The purpose of the thesis is a comprehensive and comprehensive research theoretical and practical problems of administrative and legal ensuring the safety of tourism.